Hyperglycaemia after dolutegravir-based antiretroviral treatment in people living with human immunodeficiency virus: A case series - Keerthana Sagadevan; Pilla S. Surya Durga Devi; Katikatala Swaroopa; P. Sathish Sreenivas; R. Srinivasa Rao (Journal of Clinical and Scientific Research)
Antiretroviral therapy involves a combination of human immunodeficiency virus (HIV) medicines recommended for everyone who has HIV which helps them to live longer, and healthier, and reduces the risk of HIV transmission. Dolutegravir (DTG)-based antiretroviral treatment (ART) is preferred as the first-line regimen. A recently significant number of DTG-induced hyperglycaemia cases are being reported to our adverse drug reaction monitoring centre. Here, we report on five of them from March 2022 to July 2022. All five patients who were living with HIV either started or switched to ART with a tenofovir, lamivudine and DTG (TLD) regimen based on the latest guidelines for HIV treatment by the National Acquired Immune Deficiency Syndrome Control Organization (NACO). On routine checkups, the patients were found to have raised blood sugar levels; amongst them, some patients had symptoms of diabetes. All such patients were referred to the Medicine Outpatient Department, diagnosed to have type 2 diabetes mellitus and started on appropriate treatment. The TLD regimen was continued. This was categorised as per the World Health Organization (WHO) Causality Assessment Scale as “possible” category. These cases were reported to AMC and uploaded to VigiFlow. Whenever a patient has been started on a DTG-based ART regimen, the treating physician should counsel the patient about warning signs of hyperglycaemia, recommended to do periodic screening of blood sugar levels which helps in the early diagnosis and treatment of such cases.